Ethics Beyond the Limits
1 online resource (268 pages)
Keywords: Bernard Williams’ Ethics and the Limits of Philosophy is widely regarded as one of the most important works of moral philosophy in the last fifty years. Williams’s powerful sceptical critique of the "morality system" sent shockwaves through philosophy, the implications of which are still being reckoned with thirty years later. In this outstanding collection of new essays, fourteen internationally-recognised philosophers examine the enduring contribution that Williams’s book continues to make to ethics. After a detailed topical summary of Ethics and the Limits of Philosophy by Adrian Moore, the full scope of the work is assessed, including the role of Aristotle and Hume in Williams’ thought and his arguments concerning the history of philosophy; the nature of virtue, the good life, practical reason, and deliberation; and the themes of duty, blame and inauthenticity. Ethics Beyond the Limits is required reading for students and researchers in ethics, metaethics, and moral psychology, and highly recommended for anyone studying the work of Bernard Williams.